Using insecticidal compounds to elucidate the potential role of neurotransmitters in Lepidoptera pupal ecdysis - Niranjana Krishnan; Cassandra Gorman; Jillian Stewart; Steven Bradbury; Russell Jurenka (Scientific Reports)
Abstract Previously, we reported final-instar lepidopteran larvae exposed to low doses of imidacloprid, clothianidin, and thiamethoxam had arrest in pupal ecdysis, which is a novel adverse outcome for neonicotinoid insecticides. Since neonicotinoids disrupt acetylcholine signaling, we hypothesized that the excitatory neurotransmitter acetylcholine plays a critical role in regulation of pupal ecdysis, likely by modulating the release of peptides from crustacean cardioactive peptide (CCAP) neurons. In this paper, using two lepidopteran species, we undertook studies with five additional nicotinic acetylcholine receptor (nAChR) agonists and three muscarinic acetylcholine receptor (mAChR) agonists to hypothesize the putative nAChR subunits that mediate pupal ecdysis. We also explored the potential role of mAChRs in regulation of pupal ecdysis. These findings, along with toxicokinetic analyses, suggest that pupal ecdysis may be mediated by the α1, β1, and β2 subunits of nAChRs without involvement of mAChRs. An analysis of ecdysis movements showed that neonicotinoid-treated lepidopteran larvae exhibited similar disruptions as observed in CCAP neuron-knockout Drosophila larvae. Based on findings to date, we hypothesize that acetylcholine regulates lepidopteran pupal ecdysis directly through CCAP neurons or by activating their upstream efferent inhibitory (likely GABA-releasing) neurons. Further studies are needed to elucidate the interplay between neuroendocrine hormones and neurotransmitters in lepidopteran pupal ecdysis.